The Big Questions: Mathematics - Tony Crilly (Quercus Books, 2011)
The Big Questions series is designed to let renowned experts address the 20 most fundamental and frequently asked questions of a major branch of science or philosophy. Each 3000-word essay simply and concisely examines a question that has eternally perplexed enquiring minds, and provides answers from history\\\\\\\\\\\\\\\'s great thinkers. This ambitious project is a unique distillation of humanity\\\\\\\\\\\\\\\'s best ideas. In Big Questions: Mathematics, Tony Crilly answers the 20 key questions: What is maths for? Where do numbers come from? Why are primes the atoms of maths? What are the strangest numbers? Are imaginary numbers real? How big is infinity? Where do parallel lines meet? What is the maths of the universe? Are statistics lies? Can maths guarantee riches? Is there a formula for everything? Why are three dimensions not enough? Can a butterfly\\\\\\\\\\\\\\\'s wings really cause a hurricane? Can we create an unbreakable code? Is maths beauty? Can maths predict the future? What shape is the universe? What is symmetry? Is maths true? Is there anything left to solve?